Kepuasan Pasien Rawat Jalan Ditinjau dari Kualitas Layanan Poli Gigi di UPTD Puskesmas Mayang Kabupaten Jember - Sri Wulandari; Hanif Hadinata Utama; Harmawan Teguh Saputra (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to analyze the level of outpatient satisfaction in terms of the quality of dental clinic services at the Mayang Community Health Center (Puskesmas Mayang) in Jember Regency. The research method used was a descriptive quantitative study with a survey approach. The study population consisted of 141 dental clinic patients during the last six months of 2024, with a sample of 104 respondents determined using the Slovin formula. Data were collected through a questionnaire structured based on service quality dimensions (reliability, responsiveness, assurance, empathy, and tangibles). Data were then analyzed using descriptive statistics and simple linear regression with SPSS. The results showed that the dental clinic service quality was in the good category, and patient satisfaction was in the satisfactory category. The regression analysis showed that service quality had a positive and significant effect on patient satisfaction, with a coefficient of determination of 19.1%. In conclusion, improving the quality of dental clinic services at the Mayang Community Health Center (Puskesmas Mayang) can increase patient satisfaction, although improvements are still needed in several aspects of service to achieve a more optimal level of satisfaction.  Keywords: Patient Satisfaction, Service Quality, Dental Clinic, Health Services